1983
DOI: 10.1111/j.1748-1716.1983.tb07237.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous injections of nicotine induce very rapid and discrete reductions of hypothalamic catecholamine levels associated with increases of ACTH, vasopressin and prolactin secretion

Abstract: The present findings show that nicotine given i.v. can within minutes induce increases of ACTH, vasopressin and prolactin secretion in the male rat, giving further evidence for the existence of nicotine-like cholinergic receptors involved in the regulation of these hormones. These changes were associated with rapid reductions of NA levels in the subependymal layer of the median eminence, in the nuc, dorsomedialis hypothalami and in the anterior and posterior periventricular hypothalamic area as revealed by qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Analogues of AVP such as desmopressin or lysine vasopressin have been used to treat nocturnal enuresis (bed wetting) in normal children (44) or to enhance learning and memory in mentally disabled children (45,46), respectively. Particularly disturbing is the fact that nicotine, a potent releaser of AVP (47)(48)(49)(50), can freely pass both the placental and blood-brain barriers of fetuses and their mothers alike (51,52). Given the recent rise in cigarette use among young girls and pregnant teenagers in the United States (53), it is important to understand the links among nicotine, vasopressin, and various conduct disorders observed in children of smoking mothers (54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…Analogues of AVP such as desmopressin or lysine vasopressin have been used to treat nocturnal enuresis (bed wetting) in normal children (44) or to enhance learning and memory in mentally disabled children (45,46), respectively. Particularly disturbing is the fact that nicotine, a potent releaser of AVP (47)(48)(49)(50), can freely pass both the placental and blood-brain barriers of fetuses and their mothers alike (51,52). Given the recent rise in cigarette use among young girls and pregnant teenagers in the United States (53), it is important to understand the links among nicotine, vasopressin, and various conduct disorders observed in children of smoking mothers (54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, many laboratories, including ours, have reported that nicotine, the main psychoactive component of cigarettes, is a potent stimulus for the secretion of stressresponsive hormones, such as adrenocorticotropic hormone (ACTH) (Cam and Bassett, 1983b;Conte-Devolx et al, 1981;Matta et al, 1987), prolactin (Andersson et al, 1983;Sharp and Beyer, 1986), and corticosterone (CORT) (Balfour et al, 1975;Cam and Bassett, 1983a). We further demonstrated that nicotine indirectly induces ACTH secretion from the anterior pituitary by directly activating noradrenergic areas of the nucleus tractus solitarius (Matta et al, 1998;Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, since nicotine is an extremely po tent secretagogue for ACTH [11][12][13][14], and since ACTH, too, produces an impressive re versal of the shock condition in the same experimental model [2][3][4][5][6]8], the possibility that a massive release of ACTH could partici pate in the nicotine-induced shock reversal seemed reasonably likely.…”
Section: Discussionmentioning
confidence: 99%
“…or 1-20 pg/rat intoacerebral ventricle (i.e.v.) causes within minutes an impressive release of ACTH [11][12][13][14] which, in the case of i.e.v. administration, can peak at about 9,000 pg/ml/min.…”
Section: Introductionmentioning
confidence: 99%